Sources of the history of the Jewish community in Dobrzyń nad Wisłą (1507-1939) - WITKOWSKA, Agnieszka (Historia i Świat, 2022)
No full monograph has yet been devoted to the history of the Jewish community in Dobrzyń nad Wisłą. This paper, whose subject is the almost completely unknown history of Jews from Dobrzyń in the years 1507-1939, stems not only from the author’s own interests, but also from the need to fill the above-mentioned gap. To study the topic, the author used mainly archival sources, which were the legacy of administrative and political authorities. Fragments of source materials are currently kept in the State Archive in Bydgoszcz and the State Archive in Toruń, and the branch in Włocławek. Especially noteworthy sources include: the vital records of Jewish people (1826-1936), the records of the Pomeranian Voivodeship Office in Toruń (1920-1939), the town records of Dobrzyń nad Wisłą (1917 -1937), and the records of the Board of the National Council (1950-1972). In these collections, the largest numbers of documents are extracts from birth records, official correspondence, minutes from the meetings of local authorities, and municipal inspections from the inter-war period. Apart from the above-mentioned archival collections, the author used a wide range of other source materials, for example, collections of maps kept in the Central Archives of Historical Records in Warsaw and in the District Office in Lipno, as well as very interesting items from private collections. Most of the above-mentioned sources have not yet been published.